Differential expression of the fractalkine chemokine receptor (CX(3)CR1) in human monocytes during differentiation - Panek, Cecilia Analia (Cell Mol Immunol, 2015)
Circulating monocytes (Mos) may continuously repopulate macrophage (MAC) or dendritic cell (DC) populations to maintain homeostasis. MACs and DCs are specialized cells that play different and complementary immunological functions. Accordingly, they present distinct migratory properties. Specifically, whereas MACs largely remain in tissues, DCs are capable of migrating from peripheral tissues to lymphoid organs. The aim of this work was to analyze the expression of the fractalkine receptor (CX(3)CR1) during the monocytic differentiation process. Freshly isolated Mos express high levels of both CX(3)CR1 mRNA and protein. During the Mo differentiation process, CX(3)CR1 is downregulated in both DCs and MACs. However, MACs showed significantly higher CX(3)CR1 expression levels than did DC. We also observed an antagonistic CX(3)CR1 regulation by interferon (IFN)-γ and interleukin (IL)-4 during MAC activation through the classical and alternative MAC pathways, respectively. IFN-γ inhibited the loss of CX(3)CR1, but IL-4 induced it. Additionally, we demonstrated an association between CX(3)CR1 expression and apoptosis prevention by soluble fractalkine (sCX(3)CL1) in Mos, DCs and MACs. This is the first report demonstrating sequential and differential CX(3)CR1 modulation during Mo differentiation. Most importantly, we demonstrated a functional link between CX(3)CR1 expression and cell survival in the presence of sCX(3)CL1.